GUIDED INQUIRY HELPED BY MIND MAP AND CURIOSITY TO STUDENTS’ CONCEPT UNDERSTANDING ABILITY (CUA) - Sri Juita Mahdalena Sitopu; Sri Probowati (Universitas Negeri Medan, 2017)
This study is aimed to investigate the difference between students’ concept understanding ability (CUA) taught with guided inquiry teaching model helped by mind map and direct instruction (DI).The existence of the effect of students’ curiosity with students’ CUA whether there is the interaction between guided inquiry helped by mind map and curiosity in order to develop students’ CUA. The research is quasi experiment with design two group pre-test and post-test. The population in this research is all students of class X MIA in SMA N 1 Namorambe. The sampel of the research is the students of class X MIA 1 which amounted to 30 people and the sampling techniques using sampling total.The results of the analysis data using Two Way of ANAVA showed that students’ CUA with the guided inquiry helped by mind map were better than the students with DI, CUA who had curiosity upper the average better than student’ KPK who had curiosity under the average, and there was the interaction between the guided inquiry helped by mind map and curiosity and the students’ CUA.